2001
DOI: 10.1002/1096-8628(20010422)100:2<95::aid-ajmg1235>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac findings in an individual with neurofibromatosis 1 and sudden death

Abstract: Vascular lesions in neurofibromatosis 1 (NF1) are infrequently recognised as manifestations of the disease, yet they can produce serious complications. Most individuals with NF1 vasculopathy are asymptomatic, which may contribute to underestimation of its frequency. A recent study indicates that vascular changes in individuals with NF1 contribute to mortality at younger ages. We report the sudden death of a young man with NF1. On autopsy examination there was evidence of an intramyocardial vasculopathy charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…However, none of the 2,322 NF1 individuals retrospectively assessed for cardiovascular malformation in the National Neurofibromatosis Foundation International Database had HCM [24], suggesting that routine echocardiography should form part of the surveillance regimen in NF1. At least four other single reports of the cooccurrence of HCM and NF1 [25-28] have appeared in the literature. Cardiac hypertrophy is the most common risk factor contributing to cardiovascular mortality and morbidity in NF1 patients [29].…”
Section: Resultsmentioning
confidence: 99%
“…However, none of the 2,322 NF1 individuals retrospectively assessed for cardiovascular malformation in the National Neurofibromatosis Foundation International Database had HCM [24], suggesting that routine echocardiography should form part of the surveillance regimen in NF1. At least four other single reports of the cooccurrence of HCM and NF1 [25-28] have appeared in the literature. Cardiac hypertrophy is the most common risk factor contributing to cardiovascular mortality and morbidity in NF1 patients [29].…”
Section: Resultsmentioning
confidence: 99%
“…Although NF1 is characterized by hyperproliferation and neoplasia of neural crest derivatives, affected individuals often have disorders that seem less related to the neural crest, including hypertension, renal artery stenosis, increased incidence of congenital heart disease, and vascular disorders (Hamilton et al, 2001;Rasmussen et al, 2001;Friedman et al, 2002). As neurofibromin is expressed in blood vessel endothelial and smooth muscle cells, Hamilton and Friedman (2000) suggested that NF1 vasculopathy might result from an alteration of neurofibromin function in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…According to large clinical series, both cerebral and peripheral vasculopathy in adults have a prevalence ranging from 0·4% to 6·4% . The incidence of vascular pathology is probably underestimated, as most of the vascular features are asymptomatic . However, major cardiac and cerebral vessel involvement can have life‐threatening consequences …”
Section: Discussionmentioning
confidence: 99%